Utilization of B2O3–Bi2O3–ZnO low-temperature glass-ceramics to immobilize iodine-loaded silver-coated silica-gel. Issue 32 (27th July 2021) - Yang, Jingjun; Li, Qingyuan; Ding, Congcong; He, Lili; Xue, Liang; Cheng, Wencai; Zhang, Zhentao; Wei, Guilin; Liu, Yi; Huang, Long; Xie, Yi; Lu, Xirui
Abstract : This study is dedicated to investigating the performance of B2 O3 –Bi2 O3 –ZnO low-temperature glass-ceramics to immobilize iodine-loaded silver-coated silica-gel (AgIs). Abstract : This study is dedicated to investigating the performance of B2 O3 –Bi2 O3 –ZnO low-temperature glass-ceramics to immobilize iodine-loaded silver-coated silica-gel (AgIs). Various mass fractions of iodine (15, 20, 25, and 30 wt%) in AgIs were studied. The degree of amorphization and density increased with increasing sintering temperature for all immobilization samples, where, the sample with 20 wt% iodine in AgIs presented optimal immobilization results at 600 °C. The diffraction peak area of AgI was the lowest and the degree of amorphization was the highest (0.562) for the sample with 20 wt% iodine in silver-coated silica gel when it was sintered at 600 °C. SEM-EDS results showed that two approaches contributed to the immobilization of AgIs: the first one is that AgIs participates in the formation of the glass-ceramics phase, which makes iodine uniformly immobilized in the glass mesh; the second one is that the glass-ceramics phase physically encapsulates a small range of aggregated AgI. The results of TGA-DSC analysis showed that the samples had a high water content, which facilitated the lowering of the glass transition temperature of the samples and thus the curing of iodine. Most importantly, when the sintering temperature is below 600 °C, the evaporation of iodine is minimal to negligible. The leaching results showed that the samples were highly resistant to leaching of elemental iodine. This experiment verified the feasibility and efficiency of B2 O3 –Bi2 O3 –ZnO ternary glass-ceramics to immobilize iodine-loaded silver-coated silica-gel at low temperatures.